PERAN SUMBER DAYA MANUSIA DALAM IMPLEMENTASI STRATEGI BRANDING UNTUK PENGUATAN PRODUK UMKM - Fredy Apritama Djunaidi; Adam Ahmad; Galang Febriansyah; Fadali Rahman; Wahyu Maulana (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the role of human resources (HR) in implementing branding strategies to strengthen the products of Micro, Small, and Medium Enterprises (MSMEs). The development of the digital era requires MSMEs to build strong and competitive brand identities. However, the success of branding is not solely determined by visual elements, but also by the competence, creativity, and digital literacy of the HR who manage the branding process. This research employs a descriptive qualitative approach through a literature study by reviewing eight relevant scientific journals related to HR, branding, digital marketing, and MSME innovation. The findings indicate that HR plays a strategic role in developing brand identity, managing digital content, fostering product innovation, and strengthening customer relationships, which collectively contribute to increased brand awareness and product competitiveness. Digital literacy among HR is proven to be a crucial factor in optimizing branding strategies on social media, while HR-driven innovation enhances product differentiation and brand value. This study concludes that the integration of HR competencies and branding strategies is essential for strengthening MSME products. Therefore, improving HR capabilities through training in branding and digital marketing is strongly recommended to support MSME sustainability.